Can a minimal replicating construct be identified as the embodiment of cancer? - Solé, Ricard V.; Valverde, Sergi; Rodríguez-Caso, Carlos Francisco; Sardanyés, Josep (Wiley, 2014)
Genomic instability is a hallmark of cancer. Cancer cells that exhibit abnormal chromosomes are characteristic of most advanced tumours, despite the potential threat represented by accumulated genetic damage. Carcinogenesis involves a loss of key components of the genetic and signalling molecular networks; hence some authors have suggested that this is part of a trend of cancer cells to behave as simple, minimal replicators. In this study, we explore this conjecture and suggest that, in the case of cancer, genomic instability has an upper limit that is associated with a minimal cancer cell network. Such a network would include (for a given microenvironment) the basic molecular components that allow cells to replicate and respond to selective pressures. However, it would also exhibit internal fragilities that could be exploited by appropriate therapies targeting the DNA repair machinery. The implications of this hypothesis are discussed.
Keywords: Carcinogénesis - Aspectos moleculares; Cancer; Error threshold; Microbial populations; Minimal cell; Mutator phenotype